Transforming Growth Factor β1 and Myocardial Remodeling in Patients with Chronic Heart Failure of Ischemic Genesis - N. E. Zakirova; A. N. Zakirova; D. F. Nizamova (Рациональная фармакотерапия в кардиологии)
Aim. To study the presence and nature of correlations between the level of transforming growth factor β1 (TFR-β1) and structural and functional parameters of the heart in the development of myocardial remodeling and fibrosis in patients with chronic heart failure (CHF) of ischemic origin.Material and methods. The study included 120 men with class II-IV CHF who have history of myocardial infarction, which are divided into 3 groups depending on the CHF class. The control group included 25 healthy men. Assessment of left ventricular (LV) structural-functional state was carried out by echocardiography. Investigation of TFR-β1 and N-terminal precursor indices of cerebral natriuretic peptide (NT-pro BNP) was performed by enzyme immunoassay.Results. Patients with class II-IV CHF were hyperexpression of ТФР-β1, the levels of which increased significantly as NYHA class increased and CHF progressed. The most significant structural-geometric rearrangement of LV and hyperactivation ТФР-β1 recorded in patients with class IV CHF (77.2±6.33 ng/ml with class IV CHF versus 46.7±3.74 ng/ml and 58.9±4.75 ng/ml with class II and III CHF; р< 0.05). In patients of class III-IV CHF, correlation relationships between ТФР-β1 level and echocardiographic parameters (LV myocardial mass index are established: r = 0.56, p = 0.05; end systolic volume index: r = 0.52, p = 0.05; value of LV ejection fraction: r = -0.48, p=0,05). Significant direct relationships are established in patients with class III-IV CHF between ТФР-β1 level and NT-rgo BNP levels (r=0,44; р=0,05).Conclusion. The intensity of myocardial remodeling and fibrosis processes in patients with a progressive course of CHF is related to ТФР-β1 hyperexpression and is associated with a high level of activity of natriuretic peptides.